Abundance, Sex Proportion, and Longitudinal Distribution of Parathelpusa spp in the Banjaran River, Banyumas Indonesia - Anastasia Endang Pulungsari; Anandita Ekasanti; Dian Bhagawati; Elly Tuti Winarni (Jurnal Biologi Tropis, 2023)
Information on the existence of Parathelpusa spp crabs in the Banjaran River, Banyumas Regency is still very limited, so research is needed on this matter. The aim of this study was to identify and describe species richness, sex proportion, distribution, and abundance. Sampling was taken by Cluster Random Sampling, from 5 selected stations, repeated 7 times, an interval of 2 weeks, in the period August-November 2021. Samples were taken using a hand net, fresh and brought to the laboratory for identification. The physicochemical conditions measured were air temperature, water temperature, pH, dissolved oxygen and current velocity. The richness and abundance of Parathelpusa spp species obtained was calculated based on the number of species and individuals obtained, while their presence at each station became the basis for calculating the longitudinal distribution. Correlation between physico-chemical factors of the river with species richness and abundance was analyzed using Principal Component Analysis (PCA). During the study, 158 crabs were obtained consisting of Parathelpusa convexa and P. bogorensis. Both species were found at all sampling sites and P. convexa dominated the catch. Overall and in several locations, the number of male crabs caught was higher. The existence of each species in the Banjaran River is influenced by different physicochemical factors. P. convexa is affected by bottom substrate, air temperature, and current speed, while P. Bogorensi is affected by water depth, bottom substrate, and DO. These results can be used as a reference in selecting habitats to find P. convexa and P. bogorensis in river waters.